Peningkatan kepadatan Alona sp. pada jerami padi yang difermentasi - Utami, Tiara; Pangkey, Henneke; Lantu, Sartje; Lumenta, Cyska; Salindeho, Indra R. N.; Kemer, Kurniati (e-Journal BUDIDAYA PERAIRAN, 2022)
The objective of this study was to determine the difference in density of Alona sp in fermented rice straw and unfermented rice straw media. This research was conducted at the Aquaculture Technology Laboratory and the Fish Health, Environment and Toxicology Laboratory, Faculty of Fisheries and Marine Sciences, Sam Ratulangi University, Manado, from March to June 2021.The experiment was based on four treatments, namely fermented rice straw media with Effective Microorganisms-4 (EM-4) solution, unfermented rice straw media, horse manure media and water media. The experimental design used was a completely randomized design (CRD) with 4 treatments, each treatment was repeated 3 times, so there were 12 experimental units. The results obtained are the density of Alona sp. cultured on fermented rice straw media were not significantly different from those cultured on unfermented rice straw media but significantly different from horse manure and water media. There was no significant difference between fermented straw media and unfermented straw media on the increase in density of Alona sp., apparently caused by the fermentation time of EM-4 solution of rice straw which was not long enough.